Studi kasus : Cystitis pada Kucing Tom di KandP Clinic Surabaya - Agato, Albert; Yullius, Victor; Heru, Heru (VITEK : Bidang Kedokteran Hewan, 2022)
Cystitis is an inflammation of the urinary bladder which is common in domestic animals as part of a urinary tract infection. Clinical symptoms of cystitis are lower abdominal pain on palpation, dysuria (animals show signs of pain on every attempt to urinate) and hematuria. The diagnosis of cystitis can be obtained through anamnesis, abdominal palpation, physical examination, clinical symptoms, urinalysis with sediment examination, blood chemistry examinations such as urea and creatinine levels, urine culture, uroendoscopy and ultrasound examination and radiography. stated that a biopsy can also be performed to differentiate cystitis from other diseases such as neoplasia. Blood test results show low platelets or platelets / anemia, thrombocytopenia. The results of the ultrasound examination showed a thickening of the walls of the VU